INCREASING THE IMPACT OF SERVICE SECTOR ON THE LIVING STANDARDS OF POPULATION IN INNOVATIVE ECONOMY ENVIRONMENT - Yulduz P. Urunbaeva (International Journal of Advanced Science and Technology, 2020)
At the present stage of development of Uzbekistan, it is necessary to increase the employment of the population on the basis of the development of the service sector, to develop the opportunities for the revenues from employment in various spheres and sectors of the economy to become the main source of income of the population and an important factor of its standard of living. The urgency and relevance of this problem is determined by the need to employ a working population at the current stage of the country's development, and the imbalance between demand and supply in the labor market.